(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Ingestion of illicit drug packages is a well-known method used in drug trafficking. Deaths in body stuffers are rare. We present two unusual fatal cases of body stuffer. They smuggled drugs for their own use and selling purpose. In one case, the deceased who was carrying the packages of narcotics in his hand had swallowed those packages to avoid police detention. Another deceased was suspected to ingest the illicit drug package to avoid inmates and police in the prison. The autopsy findings of these cases revealed intact packages inside the body. The packaging used in both cases was excellent. The aim of presenting these cases is, to discuss fatal outcome and describe how to detect the body stuffers.